Inflammatory Pseudotumour of the Lung: A Case Report and Literature Review. (5th December 2012) - Morar, R.; Bhayat, A.; Hammond, G.; Bruinette, H.; Feldman, C.
Abstract : We describe a patient with inflammatory pseudotumour of the lung. He was a young man who presented with haemotysis and the chest X-ray and computerized tomography were indicative of a nonbenign lesion in the right upper lobe. Excision biopsy confirmed the diagnosis of inflammatory myofibroblastic pseudotumour of the lung. This is a rare inflammatory nonneoplastic condition commonly affecting children and young adults.